Desarrollo de una metodología de elaboración de un montaje para identificar y clasificar irregularidades de una vía (2017)
"In this project, a methodology for the construction of a device which identifies and classifies road bumps and potholes is exposed . Then a simple quarter vehicle semiactive suspension model is developed, which aims to improve the passengers' comfort when a vehicle passes through a bump or a pothole." -- Tomado del Formato de Documento de Grado.